Association of ultrasound-assisted combined with conventional anatomical landmark paramedian spinal anesthesia and its impact on first pass success rate in patients with lower limb fractures- A retrospective cohort study - Congli Tian; Jing Xue; Huiyan Cui; Hongni Ding (PLoS ONE, 2025)
Background The association between ultrasound-assisted combined with conventional anatomical landmark paramedian spinal anesthesia regarding the first-pass success rate remains contentious. This study aims to clarify this relationship. Methods In this retrospective cohort analysis of 146 patients with lower limb fractures, patients were divided into two groups based on their spinal anesthesia technique:ultrasound-assisted combined with conventional anatomical landmark (median or paramedian). The primary endpoint was the first-pass success rate, while secondary endpoints included total procedure time and discomfort score. Recorded covariates encompassed sex, age, BMI, ASA class, preoperative preparation time, pre-injury physical activity, number of needle insertions, pain intensity (VAS), satisfaction score, puncture-related pain, and postoperative low back pain. Outcomes were evaluated via logistic regression. Results After adjusting for potential confounders, the ultrasound-assisted paramedian approach demonstrated a significantly higher first-pass success rate (OR = 6.11, 95% CI 2.09–17.86, P = 0.001). Secondary benefits included reduced procedure duration and improved patient comfort. Sensitivity analysis using propensity score matching confirmed the robustness of the results (E-value = 4.379), indicating minimal influence from unmeasured confounders. Conclusions In patients with lower limb fractures, ultrasound-assisted paramedian spinal anesthesia using anatomical landmarks increased first-pass success rates, reduced procedural time, and improved patient comfort compared to the median approach.